Study on the Different Anthropometric Measurements and Indicators of the Subjects Having Glucose Intolerance: Exploring the Impact of Anthropometric Measurements on Glucose Intolerance (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The goal of this study was to critical analysis of anthropometric measurements of subjects having glucose intolerance. The anthropometric measurement was measured of all subjects of both categories. These measurements includes height, weight, body mass index(BMI), mid upper arm circumference (MUAC), wrist circumference, waist circumference, hip circumference, waist–hip ratio (WHR), skin fold thickness (triceps, biceps, sub scapular and suprailiac), peripheral SFT, central SFT. In the research examination an endeavor has been made to comprehend the impact of body mass index on blood glucose levels in a populace of 802 adults’ people. Among the populace 802 adults (Male 421 Female 381) are drawn from etah district, Uttar Pradesh. The result of the present work is useful for the human services suppliers and arrangement creators from numerous points of view.